PENGEMBANGAN MEDIA PEMBELAJARAN CHATBOT BERBASIS WEB MUPEL IPS KELAS VI SD NEGERI PONCORUSO KABUPATEN SEMARANG - Hanif Dimas Handaru Mukti Istiningsih; Farid Ahmadi (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
This research aims to develop web-based chatbot learning media for social studies for class VI Poncoruso State Elementary School with ASEAN material. This research uses Research and Development (R&D) research. The research process was carried out in accordance with the ADDIE model which involved analysis, design, development and implementation stages. The result of this development effort is the existence of the CHASE Chatbot (ASEAN Chatbot) which can be accessed via a smartphone or computer device connected to the internet. The conclusion is that the use of the ADDIE model is very effective in developing this web-based Chatbot because of its systematic approach, which produces a product that is ready to use.